2013
DOI: 10.1002/etc.2315
|View full text |Cite
|
Sign up to set email alerts
|

A soil quality index for reclaimed mine soils

Abstract: The quality of soils found in mines is low if they do not receive any reclamation treatment; yet, to the authors’ knowledge, there are still no equations to evaluate the quality of metal-contaminated mine soils after the application of the most widely used reclamation treatments (planting vegetation and amending with wastes). Therefore, the purposes of the present study were 1) to propose a method for developing soil quality indexes (SQIs); 2) to develop the SQIs for 2 types of mine soils (settling pond and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(44 reference statements)
0
34
0
3
Order By: Relevance
“…As underground mining operations take place below ground, they generally do not create as much air pollution; contribute less to groundwater, surface water, and soil pollution; and are not as visually intrusive. Similar soil quality studies on mining area showed that reclamation of mine soil through plantation could improve the SQI score (Asensio et al, 2013). The ESQI-2 is also heavily weighted by the potentially toxic substances like PAHs and trace metals than the routine soil quality indicators generally used for agricultural soils.…”
Section: Principal Component Analysis-based Index (Esqi-2)mentioning
confidence: 92%
See 2 more Smart Citations
“…As underground mining operations take place below ground, they generally do not create as much air pollution; contribute less to groundwater, surface water, and soil pollution; and are not as visually intrusive. Similar soil quality studies on mining area showed that reclamation of mine soil through plantation could improve the SQI score (Asensio et al, 2013). The ESQI-2 is also heavily weighted by the potentially toxic substances like PAHs and trace metals than the routine soil quality indicators generally used for agricultural soils.…”
Section: Principal Component Analysis-based Index (Esqi-2)mentioning
confidence: 92%
“…Mine soil with a SQI > 0.500 may be considered as ecologically sustainable or reclamation is satisfactory (Mukhopadhyay et al, 2014). In metal-contaminated mine soil, the SQI was higher for the reclaimed site than the un-reclaimed areas (Asensio et al, 2013). In another reclaimed site, the quality of surface soil was higher than that of subsoil, especially after the application of mushroom-waste .…”
Section: R E Masto Et Al: Assessment Of Environmental Soil Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Means within a row followed by the same letters are not significantly different at P = <0.05. ESP = exchangeable sodium percentage; OM (LOI) = organic matter (loss on ignition); TKN = total kjedahl nitrogen; BD = bulk density a Gräfe and Klauber, 2011. b Asensio et al 2013. the seasons as co-variables, using dummy variables in both cases. The output was tested using a Monte Carlo test and was based on the full model.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies that have discussed and attempted to prioritise the most appropriate soil quality indicators (SQIs) for biological (Masto et al, 2015;Pulleman et al, 2012;Ritz et al, 2009) and physico-chemical indicators (Arshad and Coen, 1992;Asensio et al, 2013;Karlen and Stott, 1994;Masto et al, 2015;Rickson et al, 2012). This study focusses on a systematic process of selection for physical SQIs and then explores their potential for use in national monitoring schemes (e.g.…”
Section: Introductionmentioning
confidence: 99%